Quantitative Distribution of English and Indonesian Motion Verbs and Its Typological Implications: A case study with the English and Indonesian versions of the Twilight novel - Gede Primahadi Wijaya Rajeg; Utei Charaleghy Pamphila (Universitas Sanata Dharma, 2021)
This paper investigates the quantitative distribution (type and token frequencies, and type-per-token ratio [TTR]) of motion verbs found in English and Indonesian versions of the novel Twilight (Meyer, 2005; Sari, 2008). The study is contextualized within two divergent views on the typological characteristics of Indonesian lexicalization patterns of motion events. One study (Son, 2009) suggests that Indonesian behaves like English, representing a satellite-framed pattern (i.e., lexicalizing Manner of motion in the main verb) while another study (Wienold, 1995) argues for the verb-framed nature of Indonesian (i.e., lexicalizing Path of motion in the main verb). We seek to offer a quantitative perspective to these two proposals. Our study shows that, compared to English, Indonesian has significantly higher number (i.e., types) and occurrences (i.e., tokens) of Path verbs (reflecting the verb-framed pattern). Moreover, the higher TTR value of Path verbs for Indonesian shows a greater lexical diversity in the inventory of Indonesian Path verbs compared to English. In contrast, the English Manner verbs are significantly higher in number and in token frequency than Indonesian (suggesting the satellite-framed pattern), and show greater lexical diversity given the higher TTR value. While these findings lean toward supporting the verb-framed pattern of Indonesian (Wienold, 1995), we caution with the limitation of our conclusion and offer suggestions for future study.